2012
DOI: 10.1007/s10753-012-9526-6
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Toll-Like Receptors in the Pathogenesis of Myasthenia Gravis

Abstract: Toll-like receptors (TLRs), the innate immunity components, have been demonstrated to participate in multiple autoimmune diseases. However, our knowledge of the roles of TLRs in myasthenia gravis (MG) is still scarce. In this study, we detected the mRNA expression of TLR1 to TLR10 in peripheral blood mononuclear cells (PBMCs) of MG patients and the healthy controls by quantitative real-time polymerase transcription chain reaction. Our data demonstrate that aberrant expressions of TLRs exist in the PBMCs of MG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…mRNA expression of several TLRs was found to be highly altered in PBMCs obtained from MG patients in respect to non-MG patients: TLR2, TLR3, TLR4, TLR5, TLR8 and TLR9 expression was enhanced, whereas TLR1, TLR6 and TLR10 was diminished. Furthermore a correlation between TLR9 mRNA expression and MG clinical severity was observed; this envisages the potential involvement of TLR signaling pathway in MG pathogenesis [85]. Bernasconi et al [86] found that TLR4 was over-expressed in hyperplastic thymus from MG patients.…”
Section: Myasthenia Gravismentioning
confidence: 81%
See 3 more Smart Citations
“…mRNA expression of several TLRs was found to be highly altered in PBMCs obtained from MG patients in respect to non-MG patients: TLR2, TLR3, TLR4, TLR5, TLR8 and TLR9 expression was enhanced, whereas TLR1, TLR6 and TLR10 was diminished. Furthermore a correlation between TLR9 mRNA expression and MG clinical severity was observed; this envisages the potential involvement of TLR signaling pathway in MG pathogenesis [85]. Bernasconi et al [86] found that TLR4 was over-expressed in hyperplastic thymus from MG patients.…”
Section: Myasthenia Gravismentioning
confidence: 81%
“…Increasing evidence has demonstrated the correlation between the presence of altered [82,83], vitiligo [84] and myasthenia gravis (MG) [85,86] (Table 1).…”
Section: The Involvement Of Tlrs In Autoimmune Disease Onsetmentioning
confidence: 99%
See 2 more Smart Citations
“…TLRs can attach many PAMPs/DAMPs and it is thought that they may even attach regular 'self-' molecules including fibrinogen and heat shock proteins, suggesting a relation between the stereotypic inflammatory response mediated through TLRs and autoimmune diseases [106,107]. The signaling of TLRs is transduced in the cytoplasm through the Toll/IL-1 receptor domain (TIR), which is the site for docking to the cytoplasmic adaptor proteins of TIR that are important in coordinating the pathways of signal transduction after TLR as well as IL-1 receptor activation.…”
Section: Gall Bladder Cancermentioning
confidence: 99%